Цагаан сүлдийн алдагдсан дуудлагын хоёр хуулбарыг тодруулах нь - Г., Бадамсамбуу (Mongolian Studies, 2023)
Well-known Mongolian scholars B.Rinchen and Ts.Damdinsuren duplicated the sutra of White Spirit Sblde’s Eulogy (from the custody of the Vexillary) that had been remained in province of Warlord Lu (of Eljigen) in 1963 and turned into the research circulation. These duplications were observed comparatively. These duplications of the scholars are available to be considered as a certain resource for recognizing the importance and essentials of the ‘White Spirit Sblde’ which had been worshipped as the ‘Tug Spirit of Chinggis Khaan’. It is possible that the scholars’ duplications replaced ‘Amusing Sutra for Tug Sblde’ which is kept in and then lost from Central State Museum.